2020
DOI: 10.3390/cancers12061416
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Oncolytic Viruses in Randomized Controlled Trials: A Systematic Review and Meta-Analysis

Abstract: Oncolytic virotherapy is a promising antitumor therapeutic strategy. It is based on the ability of viruses to selectively kill cancer cells and induce host antitumor immune responses. However, the clinical outcomes of oncolytic viruses (OVs) vary widely. Therefore, we performed a meta-analysis to illustrate the efficacy and safety of oncolytic viruses. The Cochrane Library, PubMed, and EMBASE databases were searched for randomized controlled trials (RCTs) published up to 31 January 2020. The data for objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 49 publications
0
19
0
1
Order By: Relevance
“…However, while local OVs administration has shown promising results in melanoma patients, systemic OVs administration has reported only occasional and transient responses. 5 The inadequate delivery of OVs to the tumor, as a result of liver or spleen sequestration, immune system recognition and elimination, and poor tumor extravasation and spread, has been identified as a main factor for insufficient antitumor efficacy after systemic OVs administration. 3 It is, therefore, of clinical relevance to develop new strategies to improve OVs bioavailability and delivery to tumors, especially for those patients where intratumoral injection is not feasible or with tumor metastases.…”
Section: Introductionmentioning
confidence: 99%
“…However, while local OVs administration has shown promising results in melanoma patients, systemic OVs administration has reported only occasional and transient responses. 5 The inadequate delivery of OVs to the tumor, as a result of liver or spleen sequestration, immune system recognition and elimination, and poor tumor extravasation and spread, has been identified as a main factor for insufficient antitumor efficacy after systemic OVs administration. 3 It is, therefore, of clinical relevance to develop new strategies to improve OVs bioavailability and delivery to tumors, especially for those patients where intratumoral injection is not feasible or with tumor metastases.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the reported meta-analyses of OV therapies, this network meta-analysis had several strengths [ 35 37 ]. To date, there has been no network meta-analysis to comprehensively describe the efficacy and safety of optional OV therapies; thus, our study established comparisons among all eligible OV monotherapies and combination therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were either randomised to JX-594 and best supportive care (BSC) or BSC alone. Unfortunately, there was no Anti-tumour activity dependant on cancer cell lines and degree of ZAP deficiency [92] M1 oncolytic virus plus anti-PD-1 antibody and Apatinib…”
Section: Jx-594 (Pexa Vec)mentioning
confidence: 99%
“…However, pre-clinical studies showed disappointing efficacy highlighting the potential requirement for combination therapy and additional genetic engineering of the virus to improve efficacy. Inhibitors of valosin-containing protein have been observed to be specific inductors of oncolysis in HCC by promoting stress-induced apoptosis [92] . A phase 1 trial (NCT04665362) has now been approved to determine the safety, tolerability & efficacy of the M1 virus combined with an anti-PD-1 (SHR-1201) antibody and Apatinib, a tyrosine kinase inhibitor in patients with advanced HCC.…”
Section: Pre-clinical Hcc Ov Researchmentioning
confidence: 99%